Um olhar sobre as relações de gênero nas práticas pedagógicas dos docentes do sexo masculino de Corumbá-MS - Zozias, Rosemeiry Assunção Alves (2022)
This dissertation is linked to the Gender and Sexualities, Culture, Education and Health research line of the Postgraduate Master's Program in Education of Mato Grosso do Sul Federal University – Pantanal Campus. The general objective of the work was to investigate the gender conceptions among the male teachers of Corumbá public school system and the possible implications of those conceptions in their pedagogical practices. It is understood that school is a space that should promote discussions regarding gender issues in school practices, as these are the result of cultural, social, and political constructions. The urgent need for studies like this one is evident, considering the principles of meanings in which bodies are continuously produced in the social spheres and consequently in the school institution as reflections of culture. The theoretical framework of this study is based on the perspective of Gender and Masculinity Studies. The work was developed through bibliographic research inscribed in the qualitative methodological approach of an exploratory nature. At first, we carried out a bibliographic survey on theoretical discussions about gender issues in teaching practices. In the second moment, we carried out field research in a public school in Corumbá/MS. The study made use of an interview, with a semi-structured script to understand the gender conceptions that permeate six participant teachers’ speeches in the study. The collected data were categorized according to the content analysis proposed by Bardin. Data were organized into three categories: (i) teachers' perceptions about gender equality and sexism, (ii) teachers' positions regarding behaviors resulting from conservative perceptions; (iii) teachers' perspective on the discussion concerning gender relations in the school environment. From the data analysis, it was found that there is an emphasis on the notion of gender associated with the appropriate social roles for men and women. Regarding to teaching pedagogical practice, the study found that they are not always carried out with a view to thinking about gender relations in a critical and reflective way. Therefore, the study showed that boys and girls receive unequal treatment in the training processes by teachers. This study revealed that teachers do not feel prepared to address the issue of gender relations at school and one of the difficulties pointed out refers to the lack of initial and continuing education processes. Based on those results, we conclude that discussions on this theme are essential, whose reflection contributes to the development of plural and inclusive pedagogical alternatives that allow new perspectives on gender conceptions in school education institutions. This research becomes an invitation to extend this knowledge and transformation process.